The Relationship Between Knowledge and Compliance in Consuming Iron (Fe) Tablets with The Incidence of Anemia Among Female Adolescents at SMA N 1 Suruh - Daimatus Sholikhah; Risma Aliviani Putri (Indonesian Journal of Midwifery (IJM), 2026)
Anemia remains a significant health problem among adolescent girls, primarily due to low hemoglobin levels. Although the prevalence has declined in recent years, it is still considered relatively high according to global health standards. In several regions, from provincial to local levels, the proportion of adolescent girls affected by anemia remains substantial. In some primary healthcare service areas, the prevalence has even shown an increasing trend. One of the key contributing factors is the low level of knowledge and adherence among adolescents in consuming iron (Fe) supplements. Despite the increasing national coverage of iron tablet distribution, the proportion of adolescents who consume the recommended amount remains very low. Common reasons for non-compliance include discomfort after consumption, forgetfulness, lack of perceived benefits, and concerns about side effects. Iron supplementation programs have long been implemented as a government intervention to prevent anemia. However, their effectiveness largely depends on the behavior, awareness, and consistency of adolescents in taking the supplements regularly. = This study aims to determine the relationship between knowledge and compliance in consuming Fe tablets with the incidence of anemia among female adolescents at SMA N 1 Suruh. Research. This study used a descriptive correlational design with a cross-sectional approach. The sample consisted of 89 female students in grade XI at SMA N 1 Suruh who had undergone anemia screening. Sampling was conducted using purposive sampling. Data were collected through questionnaires to assess knowledge and compliance levels, and secondary hemoglobin data from Suruh Public Health Center. Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most respondents had low knowledge and low compliance in consuming Fe tablets. There was a significant relationship between knowledge and the incidence of anemia (p-value = 0.022, OR = 0.301), and between compliance in consuming Fe tablets and the incidence of anemia (p-value = 0.045, OR = 2.764). There is a significant relationship between the level of knowledge and compliance in consuming Fe tablets with the incidence of anemia among female adolescents. Strengthening education and consistent monitoring of Fe tablet consumption are essential to reduce anemia rates in this population.